2019
DOI: 10.1038/s41467-019-09298-4
|View full text |Cite
|
Sign up to set email alerts
|

WNT5A is transported via lipoprotein particles in the cerebrospinal fluid to regulate hindbrain morphogenesis

Abstract: WNTs are lipid-modified proteins that control multiple functions in development and disease via short- and long-range signaling. However, it is unclear how these hydrophobic molecules spread over long distances in the mammalian brain. Here we show that WNT5A is produced by the choroid plexus (ChP) of the developing hindbrain, but not the telencephalon, in both mouse and human. Since the ChP produces and secretes the cerebrospinal fluid (CSF), we examine the presence of WNT5A in the CSF and find that it is asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 68 publications
(47 reference statements)
1
73
0
Order By: Relevance
“…[24][25][26] Wnts may bind to lipoproteins that stabilize them as well. 19,27 Interestingly, macrophage-derived EVs carry Wnt proteins to ISCs in intestinal repair, 11 and we provide evidence that fibroblast-derived EVs transfer Wnt activity in the ISC niche in WT organoids as well. Importantly, we found no rescue effect with EVs when R-Spondin1 lacked from the culture medium.…”
Section: Discussionmentioning
confidence: 69%
“…[24][25][26] Wnts may bind to lipoproteins that stabilize them as well. 19,27 Interestingly, macrophage-derived EVs carry Wnt proteins to ISCs in intestinal repair, 11 and we provide evidence that fibroblast-derived EVs transfer Wnt activity in the ISC niche in WT organoids as well. Importantly, we found no rescue effect with EVs when R-Spondin1 lacked from the culture medium.…”
Section: Discussionmentioning
confidence: 69%
“…Furthermore, Wnt5a is produced in the murine choroid plexus (CP) and is required for morphogenesis of the dorsal hindbrain. Recently, it was shown that Wnt5a colocalises with lipoproteins in CP epithelial cells and target hindbrain progenitors at the ventricle, which express Wnt signalling components as well as receptors for lipoprotein particles (Kaiser et al, 2019). Although a mechanism explaining how Wnt may be loaded onto lipoproteins is yet to be determined, lipoprotein-mediated transport seems to be an important Wnt transport mechanism in the context of the cerebrospinal fluid.…”
Section: Lipoproteinsmentioning
confidence: 99%
“…It has recently emerged that the cerebrospinal fluid (CSF) contains many signals important for cell differentiation, and is an important route for the control of morphogenesis ( Fame and Lehtinen, 2020 ). The CSF is a complex liquid filling the central nervous system cavities containing a set of diffusible signaling cues guiding neurogenesis ( Lehtinen et al, 2011 ) and brain morphology in a tissue autonomous manner ( Kaiser et al, 2019 ; Langford et al, 2020 ). The CSF circulation is in part generated by the coordinated movement of cilia projecting to the lumen of brain ventricles and central canal of the spinal cord ( Faubel et al, 2016 ; Hagenlocher et al, 2013 ; Olstad et al, 2019 ; Sternberg et al, 2018 ; Thouvenin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%